Awareness of palliative care among general practioners of Bhopal: a cross sectional study - Roopesh Jain; Bhupendra Kumar Ratre; Narmada Prasad Patel (International Journal of Medical Research and Review, 2017)
Introduction: Palliative medicine is one of the developing medical specialities. This study was undertaken to enquire about the level of awareness regarding various aspects of palliative care among general practitioners of city of Bhopal.Material and method: This study was undertaken with the help predesigned questionnaire among the general practioners enquiring them about various aspects of Palliative medicine.Results: The opinion about diseases requiring palliative care varied to large extent. Majority of subject reported pain control as the main objective of palliative care. There were varied response to various other aspects of palliative care but majority had considered it important.Discussion: Palliative care is an important aspect of comprehensive care which needs to be given to terminally ill patients. Awareness regarding same variable even among doctors and improved awareness through various means is essential to improve quality of life of patients and their families facing the problems associated with life-threatening illness.